From stroke mimic to genetic enigma: diagnostic challenges in neuronal intranuclear inclusion disease associated with FMR1 premutation - Hameed, Shahana Shahul (International Journal of Research in Medical Sciences, 2025)
Neuronal intranuclear inclusion disease (NIID) is a rare progressive neurodegenerative disorder characterized by eosinophilic hyaline intranuclear inclusions in neurons, glial cells, and visceral organs. Recently, NIID has been genetically linked to GGC repeat expansion in the 5′-UTR of the NOTCH2NLC gene. Interestingly, overlapping imaging and clinical features have been observed with fragile X-associated tremor/ataxia syndrome (FXTAS), caused by fragile X messenger ribonucleoprotein 1 (FMR1) premutation. A 52-year-old male with long-standing diabetes and hypertension presented with multiple recurrent episodes of transient loss of consciousness over 12 years, mimicking vertebrobasilar transient ischemic attacks. He later developed transient quadriplegia and dysarthria with complete recovery within hours. Initial MRI showed diffusion restriction in the right corona radiata, reported as acute infarct. Repeat MRI and CT angiogram revealed diffusion restriction and FLAIR hyperintensities in the frontoparietal white matter at corticomedullary junctions, corpus callosum, and bilateral middle cerebellar peduncles. Skin biopsy showed intranuclear inclusions in sweat gland cells. Genetic analysis confirmed FMR1 premutation with 99 CGG repeats, establishing the diagnosis of FXTAS with overlapping features of NIID. This case emphasizes the diagnostic challenge in distinguishing NIID from FXTAS, both of which share overlapping clinical and MRI features. Genetic testing for FMR1 mutations should be considered in patients with stroke-like or episodic neurogenic events showing corticomedullary DWI hyperintensities and intranuclear inclusions on biopsy.